2020
DOI: 10.24235/tarbawi.v5i2.6721
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pemanfaatan Media Pembelajaran Online Di SMK It Rabbi Radhiyya Masa Pandemi Covid-19

Abstract: Almost all circles of society in the world today are shadowed by an extraordinary fear of the plague that hits the world or the so-called the pandemic. In early 2020, Indonesia even also felt the same thing, and this has an implication for the issuance of several government policies in an effort to minimize the spread of the covid-19 outbreak by giving an appeal to the community to limit gatherings including school activities by switching them to the application of work from home (WFH) learning. In response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 3 publications
1
3
0
11
Order By: Relevance
“…The learning processes utilized electronic devices, such as cellphones with some applications therein, which a stable internet connection must accompany. As a confirmative context, similar findings are also encountered in Elisvi's et al (2020) and Warsah's (2021) studies on learning processes in Indonesia's online learning context. The observation data confirmed that learning generally began with greetings, prayer, and checking for students' presence.…”
Section: The Process Of Conducting Online Classes During the Covid-19 Pandemic At Ma Muhammadiyah Kampung Delimasupporting
confidence: 80%
“…The learning processes utilized electronic devices, such as cellphones with some applications therein, which a stable internet connection must accompany. As a confirmative context, similar findings are also encountered in Elisvi's et al (2020) and Warsah's (2021) studies on learning processes in Indonesia's online learning context. The observation data confirmed that learning generally began with greetings, prayer, and checking for students' presence.…”
Section: The Process Of Conducting Online Classes During the Covid-19 Pandemic At Ma Muhammadiyah Kampung Delimasupporting
confidence: 80%
“…Di belahan bumi manapun, corona masih mendominasi ruang publik. Dalam waktu singkat saja, namanya menjadi trending topik, dibicarakan di sana-sini, dan diberitakan secara masif di media cetak maupun elektronik (Elisvi et al, 2020;Uyun & Warsah, 2021b;Warsah, 2021). Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) yang lebih dikenal dengan nama virus corona adalah jenis baru dari coronavirus yang menyebabkan penyakit menular ke manusia, terlebih lagi telah ditemukannya varian baru yang lebih ganas dari varian-varian sebelumnya yaitu varian Delta dari India (Hartono & Yusuf, 2021;Riley et al, 2021).…”
Section: Pendahuluanunclassified
“…Virus ini menular sangat cepat dan telah menyebar hampir ke semua negara, termasuk Indonesia, hanya dalam waktu beberapa bulan saja. Sehingga WHO pada tanggal 11 Maret 2020 menetapkan wabah ini sebagai pandemi global (Elisvi et al, 2020;Meliza et al, 2020).…”
Section: Pendahuluanunclassified
“…COVID-19 is a dangerous epidemic. All elements of human life on earth are disrupted, including in the world of education (Elisvi et al, 2020;Robandi et al, 2020). Rejang Lebong Regency, Bengkulu province, decided to close schools.…”
Section: Introductionmentioning
confidence: 99%